2009
DOI: 10.5012/bkcs.2009.30.9.2051
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Study of Malachite Green Fading in the Presence of TX-100, DTAB and SDS

Abstract: The rate constants of alkaline fading of malachite green (MG + ) was measured in the presence of nonionic (TX-100), cationic (DTAB) and anionic (SDS) surfactants. This reaction was studied under pseudo-first-order conditions at 283∼303 K. The rate of fading reaction showed noticeable dependence on the electrical charge of the used surfactants. It was observed that the reaction rate constants were increased in the presence of TX-100 and DTAB and decreased in the presence of SDS. According to Hughs-Ingold rules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…13,14 There are reports of investigations into the interactions between carbocation dyes and oppositely charged surfactants both in the pre- 15−17 and postmicellar 15 region. The kinetic investigations of the alkaline fading of malachite green have been reported in the presence of micelles 18,19 and reverse micelle. 19 Spectral and surface tension measurement studies on the premicelle formation behavior of several carbocation dyes with different anionic surfactants such as sodium dodecyl sulfate (SDS), sodium dodecyl benzenesulfonate (SDBS), and sodium dodecyl sulfonate (SDSN) have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 There are reports of investigations into the interactions between carbocation dyes and oppositely charged surfactants both in the pre- 15−17 and postmicellar 15 region. The kinetic investigations of the alkaline fading of malachite green have been reported in the presence of micelles 18,19 and reverse micelle. 19 Spectral and surface tension measurement studies on the premicelle formation behavior of several carbocation dyes with different anionic surfactants such as sodium dodecyl sulfate (SDS), sodium dodecyl benzenesulfonate (SDBS), and sodium dodecyl sulfonate (SDSN) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Microenvironments consisting of surfactants change the physicochemical behavior of the system and may either catalyze or inhibit the rates of different reactions. Such catalysis or inhibition may occur by decreasing the entropy of the reactants either due to their association with the micelle or due to preferential interaction between the substrates and the micelle, thereby promoting or inhibiting the approach of the reactants toward themselves. This type of rate modulation is also often observed in the submicellar concentrations of surfactant owing to the specific interaction between the reactant and the surfactant monomer resulting in the formation of premicellar aggregates. , There are reports of investigations into the interactions between carbocation dyes and oppositely charged surfactants both in the pre- and postmicellar region. The kinetic investigations of the alkaline fading of malachite green have been reported in the presence of micelles , and reverse micelle . Spectral and surface tension measurement studies on the premicelle formation behavior of several carbocation dyes with different anionic surfactants such as sodium dodecyl sulfate (SDS), sodium dodecyl benzenesulfonate (SDBS), and sodium dodecyl sulfonate (SDSN) have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…A further increase of the surfactant concentration could lead to a decrease of the reaction rate since the methyl decanoate is diluted with higher amount of surfactant. This trend was also shown by other researchers, e.g., for the fading of dyes. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Different studies concluded the important fungal effect against oomycete fungus such as Saprolegnia [17], Haliphthoros [18] or Aphanomcyces invades [19]. Due to its effects on health, numerous studies in the literature analyze the physical-chemical properties of this compound [14,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%